IDNLearn.com: Your trusted source for accurate and reliable answers. Ask your questions and receive comprehensive and trustworthy answers from our experienced community of professionals.

Choose the justification for each step in the solution to the given equation.

[tex]\[
\begin{array}{|c|c|}
\hline
\text{Step} & \text{Statement} \\
\hline
1 & \frac{1}{4} x - \frac{9}{4} x - 7 = -15 \\
2 & -2x - 7 = -15 \\
3 & -2x - 7 + 7 = -15 + 7 \\
4 & -2x = -8 \\
5 & \frac{-2x}{-2} = \frac{-8}{-2} \\
6 & x = 4 \\
\hline
\end{array}
\][/tex]


Sagot :

Sure, let's provide detailed justifications for each step in the solution to the given equation.

1. \(\frac{1}{4} x - \frac{9}{4} x - 7 = -15\)
- Statement: This is the original equation given.

2. \(-2 x - 7 = -15\)
- Justification: Combine the like terms \(\frac{1}{4} x\) and \(\frac{9}{4} x\). Since \(\frac{1}{4} x - \frac{9}{4} x = -2 x\), the equation simplifies to \(-2 x - 7 = -15\).

3. \(-2 x - 7 + 7 = -15 + 7\)
- Justification: Add 7 to both sides of the equation to isolate the term with \(x\). This is a step to get rid of the constant term on the left side.

4. \(-2 x = -8\)
- Justification: Simplify both sides of the equation after adding 7 to \(-15\) gives \(-8\).

5. \(\frac{-2 x}{-2} = \frac{-8}{-2}\)
- Justification: Divide both sides of the equation by \(-2\) to solve for \(x\).

6. \(x = 4\)
- Justification: Simplify \(\frac{-8}{-2}\) to get \(x = 4\).

So each step follows logically from the previous by applying basic algebraic principles of combining like terms, isolating the variable term, and solving for the variable.